Diseño de un sistema de gestión integrado en la constructora "MASTER". - Hidalgo Aguilera, Luis Armando (2010)
This work is the design of an Integrated Management System for the Master Builder in the city of Quito, the main purpose of this company provide a modern management tool, which allows them to increase their productivity and hence competitiveness a once it is implemented totally. For this design creates a theoretical framework, based on the guidelines to international standards ISO9001: 2008, ISO14001: 2004 and OHSAS 18001: 2007 pose with the objective of methodological and technical guidance in the preparation of such documents. It exploits the correspondence the same ISO has in its papers on the different requirements of these three rules. To begin to design a diagnosis of productive activities currently being undertaken by construction, by which the state is able to determine which are the aspects of quality, environment, safety and occupational health, and measures taken when any of these aspects did not meet the customer, or the administration or its workers, or society in general. After studying all productive activities and identified the main problems the necessary documentation is designed as determining the rules taken as a reference for an integrated management aspects of quality, environment, safety and occupational health. This means the creation of procedures, instructions, forms; arrays with the purpose of all production activities carried out by the Builder are made effectively and are properly recorded to assess the improvement and management to present evidence of any entity that needs it.